2016
DOI: 10.1074/jbc.m115.709261
|View full text |Cite
|
Sign up to set email alerts
|

The METTL20 Homologue from Agrobacterium tumefaciens Is a Dual Specificity Protein-lysine Methyltransferase That Targets Ribosomal Protein L7/L12 and the β Subunit of Electron Transfer Flavoprotein (ETFβ)

Abstract: Human METTL20 is a mitochondrial, lysine-specific methyltransferase that methylates the ␤-subunit of electron transfer flavoprotein (ETF␤). Interestingly, putative METTL20 orthologues are found in a subset of ␣-proteobacteria, including Agrobacterium tumefaciens. Using an activity-based approach, we identified in bacterial extracts two substrates of recombinant METTL20 from A. tumefaciens (AtMETTL20), namely ETF␤ and the ribosomal protein RpL7/L12. We show that AtMETTL20, analogous to the human enzyme, methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…2C). In addition we detected after longer exposures weak automethylation of METTL12 similar to what has been observed for many other KMTs (12,17,20,33). In summary, these results show that METTL12 is a mitochondrial enzyme with protein MTase activity.…”
Section: Human Mettl12 Methylates Mitochondrial Citrate Synthasesupporting
confidence: 88%
See 1 more Smart Citation
“…2C). In addition we detected after longer exposures weak automethylation of METTL12 similar to what has been observed for many other KMTs (12,17,20,33). In summary, these results show that METTL12 is a mitochondrial enzyme with protein MTase activity.…”
Section: Human Mettl12 Methylates Mitochondrial Citrate Synthasesupporting
confidence: 88%
“…First, NaCl concentration was reduced to 50 mM by diluting cell lysates with dilution buffer (50 mM Tris-HCl, pH 7.4, 5% glycerol), and then extracts were applied onto S-column equilibrated in dilution buffer. Material bound to the S-column was eluted in 100-l aliquots by a step gradient of increasing NaCl concentrations prepared in dilution buffer, similarly as previously described (33).…”
Section: Preparation and Fractionation Of Cell Extractsmentioning
confidence: 99%
“…We have previously shown that several recombinant 7BS KMTs can methylate specific proteins when added to a cellular extract and that KMT substrates can be identified by fractionation of the extract ( 8 , 14 , 36 ). Moreover, such methylation is often strongly enhanced in extracts from cells that lack the relevant KMT, due to an increased level of unmethylated substrate ( 6 , 36 , 37 ). Thus, to investigate the potential protein MTase activity of eEF1A-KMT4, protein extracts from EEF1AKMT4 -deficient and WT HAP-1 cells were incubated with recombinant eEF1A-KMT4 and [ 3 H]AdoMet.…”
Section: Resultsmentioning
confidence: 99%
“…One example of a method that falls into this category are peptide arrays that have been used over the years to map out substrate specificity profiles for SET enzyme family members and have revealed many non-histone substrates, some of which have been validated through complementary cell-based analysis (Dhayalan et al, 2011;Lanouette et al, 2015;Rathert et al, 2008;Schuhmacher et al, 2015;Weirich et al, 2016). Other successful approaches for the identification of PKMT substrates are protein interaction analyses aiming to identify novel binding substrates, which are then candidates for methylation studies (Ahmed et al, 2016;Cloutier et al, 2013;Davydova et al, 2014;Jakobsson et al, 2013;Kernstock et al, 2012;Lanouette et al, 2015), and biochemical purification of methylated proteins either based on enzyme activity (Malecki et al, 2015(Malecki et al, , 2016 or using methyl lysine-specific antibodies or binding domains (Cao et al, 2013;Moore et al, 2013). Moreover, cellular protein labeling studies with modified AdoMet have been employed to identify PKMT substrates (Shimazu et al, 2014), and SILAC studies with wild-type and PKMT knockout cell lines have provided the first proteome-wide collections of PKMT substrates (Carlson et al, 2015;Olsen et al, 2016).…”
Section: Methods For the Identification Of Pkmt Substratesmentioning
confidence: 99%
“…Dot1L is a prominent member of the 7BS group known to methylate histone H3 at K79 (Feng et al, 2002;van Leeuwen et al, 2002). However, recent studies have identified 7BS methyltransferases that have non-histone protein substrates, and their initial candidate substrates were often identified by protein interaction studies and later validated biochemically (Davydova et al, 2014;Jakobsson et al, 2013;Kernstock et al, 2012;Malecki et al, 2015Malecki et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%